Visitors' use and understanding of interactive exhibits and learning of scientific concepts. - McClafferty, Terence P. (Curtin University, 2000)
Visitors use and understanding of interactive exhibits and their learning of scientific concepts was investigated by three studies. The first study categorised visitors' use of a sound exhibit and found that 49% successfully used the exhibit. Understanding was described with a knowledge hierarchy and learning was measured using a pre-test and post-test. Findings indicated that many visitors had prior knowledge of the relevant concepts and 50% of visitors learnt a concept from the exhibit. The second study investigated young children's understanding and interaction with the Mitey Quarry, a cooperative exhibit of four elements, conveyor, elevator, auger and sorter, which were used to move balls around the exhibit. Findings indicated that children's activities and their level of understanding varied for each element, though higher levels were achieved with elements that were easily observable. The children's activities began with observation, and then vacillated between manipulation, operation and control of an element. The third study identified the educational objectives of a physical fitness exhibit, Let's Get Physical, and their achievement by high school students. Findings indicated that the instructional sequence integrated cognitive and affective objectives, and although 42% of students stated their intentions to begin new exercise activities in response to the exhibit message "to be active everyday", after two weeks, these intentions had not been enacted. The research has contributed to improved exhibit design by demonstrating the value of knowledge, activity and affective hierarchies in identifying exhibit objectives and providing a means for evaluation. Hierarchies are an effective way to describe and measure the visitors' use and understanding of interactive exhibits and learning from them.